Cracking the IT architect interview : the ultimate guide to successful interviews for enterprise, business, domain, solution, and technical architect roles as well as IT advisory consultant and software designer roles /: the ultimate guide to successful interviews for enterprise, business, domain, solution, and technical architect roles as well as IT advisory consultant and software designer roles. (2016) - Paradkar, Sameer
No abstract available